Los hábitos de estudios y su incidencia en el rendimiento académico en el quinto año de educación básica de la escuela “General Alberto Amores” del cantón La Maná provincia Cotopaxi durante el período lectivo 2012-2013 - Gutiérrez García, Mayra Sara (2013)
Study habits are acquired by performing the same activity daily. Unfortunately, in educational institutions children are not motivated in getting them. That is why it is an issue of great importance in educational system. In order to get the objective, parents and teachers should work together for encouraging students to acquire good habits at the moment of doing homework or study. For that reason, this research was based in developing a proposal to implement a training program where a methodological guide is created with study techniques for teachers. According to this, techniques could be used by teachers to teach their students the different ways of studying and what the accurate environment is to do it. On the other hand the improvement of children’s academic performance at “General Alberto Amores" school will be evident. Inside the development of the proposal, as a first fact; it was carried out the development of the thesis where the improvement of theoretical aspects, characterization of the object of study, the application of surveys, the use of research, and the application of diverse methods permitted to identify the existing problem. Finally, the design of the proposal was presented to help improving the academic performance.